Left hemidiaphragmatic elevation: Value of histology - Seiichiro Inoue; Akio Odaka; Yuki Muta; Yuta Takeuchi; Takahisa Yamashita; Kazuhiko Kabe; Yoshio Sakurai (Elsevier, 2020)
Two neonates presented with left hemidiaphragmatic elevation. Case 1 was a boy transferred to our center at age 3 d. Asymptomatic congenital diaphragmatic eventration (CDE) was suspected. At 8 months, chest computed tomography (CT) revealed persistent left hemidiaphragmatic elevation, and surgical treatment was performed. Immunohistochemistry (IHC) of a resected membranous part of the left hemidiaphragm showed that it contained desmin-positive muscle fibers. Collagen bundles were detected by Elastica van Gieson (EvG) staining. Case 2 was a boy delivered at 38 weeks 3 d gestational age. Fetal ultrasonography and MRI had suggested left hemidiaphragmatic elevation, suspicious for CDE. His Apgar scores were 8 and 6 at 1 minute and 5 minutes. He was intubated immediately after delivery. Weaning from ventilation was unsuccessful and surgery was performed 21 d after delivery. Partial resection of the membranous part and repair of the muscular hemidiaphragm were performed. EcG staining revealed collagen bundles, even though desmin-positive muscle fibers were not seen on IHC. Muscle fibers and collagen bundles are two important components of the diaphragm, and are not found in either the pleura or peritoneum. Accordingly, CDE was diagnosed in both cases. EvG suggested the diagnosis.